2010
DOI: 10.1186/1742-6405-7-18
|View full text |Cite
|
Sign up to set email alerts
|

Generic and low dose antiretroviral therapy in adults and children: implication for scaling up treatment in resource limited settings

Abstract: Although access to antiretroviral therapy (ART) for the treatment of HIV has increased during the last decade, many patients are still in need of treatment. With limited funds to provide ART to millions of patients worldwide, there is a need for alternative ways to scale up ART in resource limited settings. This review provides an overview of pharmacokinetic, safety and efficacy studies of generic and reduced dose ART. The production of generic ART has greatly influenced the decline in drug prices and the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…24 Thai patients, on the contrary, in a study evaluating tenofovir/emtricitabine (TDF/FTC) plus EFV had lower rate of EFV-related neuropsychiatric disturbances than those reported in developed countries, while renal toxicity due to TDF was higher than in the published literature. 25 As reported also by others, 26 a low proportion of women enrolled in registrative trials was observed in the present analysis (19.2%); although it is interesting that a higher percentage of women was enrolled in multicentre trials conducted in at least one developing than in those conducted only in developing country. Women account for half of all people living with HIV worldwide, and nearly 60% of HIV infections in sub-Saharan Africa, 9 and it is therefore noteworthy that women be adequately represented in clinical trials, particularly in those regions where they account for the majority of patients.…”
Section: Discussionsupporting
confidence: 80%
“…24 Thai patients, on the contrary, in a study evaluating tenofovir/emtricitabine (TDF/FTC) plus EFV had lower rate of EFV-related neuropsychiatric disturbances than those reported in developed countries, while renal toxicity due to TDF was higher than in the published literature. 25 As reported also by others, 26 a low proportion of women enrolled in registrative trials was observed in the present analysis (19.2%); although it is interesting that a higher percentage of women was enrolled in multicentre trials conducted in at least one developing than in those conducted only in developing country. Women account for half of all people living with HIV worldwide, and nearly 60% of HIV infections in sub-Saharan Africa, 9 and it is therefore noteworthy that women be adequately represented in clinical trials, particularly in those regions where they account for the majority of patients.…”
Section: Discussionsupporting
confidence: 80%
“…The numbers of children in the three darunavir/ritonavir weight band twicedaily dosing groups were 12 children for 375/100 mg (20 to <30 kg), 2 children for 450/100 mg (30 to <40 kg) and 5 children for 600/100 mg (≥40 kg). The median (IQR) duration on darunavir/ritonavir was 11 months (6)(7)(8)(9)(10)(11)(12)(13). Other antiretroviral drugs in the regimen were tenofovir (63%), zidovudine (58%), abacavir (5%), lamivudine (95%) and etravirine (42%).…”
Section: Resultsmentioning
confidence: 99%
“…There were two patients on anticonvulsants for >10 months prior to the pharmacokinetics sampling. One child (body weight 20.3 kg, 375/100 mg dosing) was on phenytoin 100 mg once daily and had an AUC 0-12 of 210 h×mg/l and C 12…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiretroviral dose reduction has been one of the options used in Thailand to decrease cost and increase access. Several studies have shown that Thai adults and children on low-dose antiretroviral regimens achieve comparable pharmacokinetic parameters and treatment outcomes to those of Westerners on standard doses (2,3,6,13,17). Therefore, we conducted this study to evaluate the pharmacokinetics of low-dose, once-daily raltegravir (400 mg QD) in HIV-1-infected Thai adults.…”
mentioning
confidence: 99%